Adaptive unstructured mesh modelling of multiphase flows - Xie,Z; Pavlidis,D; Percival,JR; Gomes,JLMA; Pain,CC; Matar,OK (International Journal of Multiphase Flow, 2014)
© 2013 Elsevier Ltd. Multiphase flows are often found in industrial and practical engineering applications, including bubbles, droplets, liquid film and waves. An adaptive unstructured mesh modelling framework is employed here to study interfacial flow problems, which can modify and adapt anisotropic unstructured meshes to better represent the underlying physics of multiphase problems and reduce computational effort without sacrificing accuracy. The numerical framework consists of a mixed control volume and finite element formulation, a 'volume of fluid'-type method for the interface capturing based on a compressive control volume advection method and second-order finite element methods. The framework also features a force-balanced algorithm for the surface tension implementation, minimising the spurious velocities often found in such flows. Numerical examples of the Rayleigh-Taylor instability and a rising bubble are presented to show the ability of this adaptive unstructured mesh modelling framework to capture complex interface geometries and also to increase the efficiency in multiphase flow simulations.